Transcriptional Profiling Defines Histone Acetylation as a Regulator of Gene Expression during Human-to-Mosquito Transmission of the Malaria Parasite Plasmodium falciparum - Ngwa, Che J.; Kiesow, Meike J.; Papst, Olga; Orchard, Lindsey M.; Filarsky, Michael; Rosinski, Alina N.; Voss, Till S.; Llinás, Manuel; Pradel, Gabriele (Frontiers in Cellular and Infection Microbiology, 2017)
Transmission of the malaria parasite Plasmodium falciparum from the human to the mosquito is mediated by the intraerythrocytic gametocytes, which, once taken up during a blood meal, become activated to initiate sexual reproduction. Because gametocytes are the only parasite stages able to establish an infection in the mosquito, they are crucial for spreading the tropical disease. During gametocyte maturation, different repertoires of genes are switched on and off in a well-coordinated sequence, pointing to regulatory mechanisms of gene expression. While epigenetic gene control has been studied during erythrocytic schizogony of P. falciparum, little is known about this process during human-to-mosquito transmission of the parasite. To unveil the potential role of histone acetylation during gene expression in gametocytes, we carried out a microarray-based transcriptome analysis on gametocytes treated with the histone deacetylase inhibitor trichostatin A (TSA). TSA-treatment impaired gametocyte maturation and lead to histone hyper-acetylation in these stages. Comparative transcriptomics identified 294 transcripts, which were more than 2-fold up-regulated during gametocytogenesis following TSA-treatment. In activated gametocytes, which were less sensitive to TSA, the transcript levels of 48 genes were increased. TSA-treatment further led to repression of 145 genes in immature and mature gametocytes and 7 genes in activated gametocytes. Up-regulated genes are mainly associated with functions in invasion, cytoadherence, and protein export, while down-regulated genes could particularly be assigned to transcription and translation. Chromatin immunoprecipitation demonstrated a link between gene activation and histone acetylation for selected genes. Among the genes up-regulated in TSA-treated mature gametocytes was a gene encoding the ring finger (RING)-domain protein PfRNF1, a putative E3 ligase of the ubiquitin-mediated signaling pathway. Immunochemistry demonstrated PfRNF1 expression mainly in the sexual stages of P. falciparum with peak expression in stage II gametocytes, where the protein localized to the nucleus and cytoplasm. Pfrnf1 promoter and coding regions associated with acetylated histones, and TSA-treatment resulted in increased PfRNF1 levels. Our combined data point to an essential role of histone acetylation for gene regulation in gametocytes, which can be exploited for malaria transmission-blocking interventions.